Effect Of Microencapsulated Lactobacillus Plantarum On The Rheological And Sensorial Properties Of Synbiotic Ice Cream - Siti Radhiah Binti Omar; Siti Nazirah Omar (Vibus Innovative Publishing Solutions, 2024)
Synbiotic ice creams formulated with three probiotic variations (free L. plantarum, encapsulated L. plantarum, and a mixture of commercial Bifido. Sp and L. plantarum) were observed for their rheology and sensory properties. Microencapsulation of L. plantarum isolated from fermented cacao beans via freeze drying with 6% (w/v) lactose, 6% (w/v) skim milk and 3% solution of k-carrageenan coatings has shown the highest viscoelastic properties based on high fat content due to the addition of vegetable oil during the encapsulation process. Although there was no significant differences (p<0.05) in the overall acceptance attributes, the degree of sweetness for encapsulated L. plantarum ice cream was significantly higher (p<0.05) when compared to other samples. Henceforth, the encapsulation materials and freeze drying technique did improve the viscoelastic properties and overcome the sour taste of probiotics in ice cream formulation.